Caducidad de la acción de despido ineficaz en la mujer embarazada - Correa Guzmán, Stefania Alexandra (2018)
In 2015, the Law for Labor Justice and Recognition of Work in the Home was published in the Official Gazette of Ecuador, which contains several amendments to the Labor Code and in one of those of article 195, extending it to three sub-articles, which deal with everything related to the Ineffective Dismissal that takes effect only in cases of untimely dismissal of pregnant women and union leaders, and whose main purpose is the restitution of the affected person plus the payment of all outstanding remunerations with a 10% surcharge, or if the affected person does not wish to return to his job, he must be paid one year of the remuneration he was receiving plus the compensation for untimely dismissal. Article 195.2 subsection 1 of the current Labor Code establishes the deadline for filing an action for ineffective dismissal, which is 30 days after untimely dismissal, a term that is very limited for pregnant women. since it is too short to access the guarantees that this legal figure offers since certain circumstances could arise that do not depend on the pregnant woman and prevent her from preparing a good defense, and succeed in presenting the dismissal action ineffective in the established time, or on the other hand, you may be able to file the action of ineffective dismissal within thirty days but without sufficient evidence taking your process in the labor court to file. In September 2016, the Official Registry of Ecuador published the resolution 05-2016 entitled justification of the draft resolution of the plenary session issued by the National Court of Justice, which empowers judges of the Labor Judicial Unit to declare ex officio the expiration of the action for ineffective dismissal for the passage of time established by the Labor Code to present it, affecting the right that people have and among them pregnant women due process established in Article 76 of the Constitution of the Republic…….